"Did you wash your hands?": a prospective study of patient empowerment to prompt hand washing by healthcare providers. Issue 5 (September 2021) - Eng, Tony Y; Eng, Nina L; Jenkins, Carol A; Grota, Patti G
Background: Hand hygiene is paramount in preventing the spread of healthcare-associated infections especially during disease epidemics. Compliance rates with hand hygiene policies remain below 50% internationally and may be lower in the outpatient care setting. This study assessed the impact of the patient empowerment model on hand hygiene compliance among healthcare providers. Methods: From October 2016 to May 2017, patients from a large ambulatory oncology centre were prospectively enrolled. Patients were instructed to observe healthcare providers for hand hygiene compliance and to remind healthcare providers where it was not observed during at least three consecutive encounters. Healthcare provider reactions to this intervention were rated by patients. Patients' hand hygiene knowledge and beliefs were objectively elicited pre and post-study. Results: Thirty patients with a median age of 52 years (range 5–91) completed the study for a total of 190 healthcare provider encounters. When initial hand hygiene was not observed, patients offered a reminder in 71 (37.4%) encounters, did not offer a reminder in 73 (38.4%) encounters and forgot to offer a reminder in 24 (14.2%) encounters. Patients perceived positive or neutral reactions in 76.8% of encounters and negative or surprised reactions in 23.2% of encounters. Healthcare provider compliance improved from 11.6% to 48.9% with intervention. Patient hand hygiene knowledge improved by 16% following the study. Conclusions: Patient-empowered hand hygiene may be a useful adjunct for improving hand hygiene compliance among healthcare providers and improving patient hand hygiene knowledge, although it may confer an emotional burden on patients.